Analysis of the Effects of Banking Credit, Inflation, Government Expenditure, and Absorption of Labor on Economic Growth and Poverty Levels in Indonesia - Devita Prasasti; Andrie Elia Embang; Miar Bakar (Fakultas Ekonomi dan Bisnis Universitas Palangka Raya, 2019)
This study aims to analyze the factors that influence economic growth and poverty levels inIndonesia. The factors analyzed were banking credit, inflation, government expenditure, andabsorption of labor. This research uses path analysis as a data analysis technique to answerresearch problems / hypotheses. Research results show that (1) Banking credit towards economicgrowth shows significant value, (2) Inflation towards economic growth shows significant value,(3) Government expenditures on growth shows significant value, (4) Labor absorption oneconomic growth shows significant value, (5) Banking credit towards poverty level showssignificant value, (6) Inflation to poverty level shows significant value, (7) Governmentexpenditures on poverty level shows significant value, (8) Absorption of labor to poverty level shows significant value, ( 9) Economic growth towards the poverty level shows significant value,(10) Banking credit does not significantly influence the level of poverty through economicgrowth, (11) Inflation has a significant effect on the level of poverty through economic growth,(12) Government expenditure has a significant effect on the level of poverty through economicgrowth, (13) Absorption of labor has a significant effect on poverty levels through economicgrowth.